2019
DOI: 10.1136/bmjopen-2018-026075
|View full text |Cite
|
Sign up to set email alerts
|

Does enhanced physical rehabilitation following intensive care unit discharge improve outcomes in patients who received mechanical ventilation? A systematic review and meta-analysis

Abstract: ObjectiveWe aimed to determine whether enhanced physical rehabilitation following intensive care unit (ICU) discharge improves activities-of-daily-living function, quality of life (QOL) and mortality among patients who received mechanical ventilation in the ICU.DesignSystematic review and meta-analysis using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach.Data sourcesMEDLINE, Embase, CENTRAL, PEDro and WHO International Clinical Trials Registry Platform searched through J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 38 publications
0
28
0
2
Order By: Relevance
“…Fourth, while it seemed that patients with ICUAW recovered, this observational study can draw no conclusions about possible interventions. Given that post-ICU rehabilitation presently lacks evidence to improve quality of life [46], the pathways of recovery need further investigation. A prospective mixed-methods cohort study might reveal possible interventions to target for future studies.…”
Section: Plos Onementioning
confidence: 99%
“…Fourth, while it seemed that patients with ICUAW recovered, this observational study can draw no conclusions about possible interventions. Given that post-ICU rehabilitation presently lacks evidence to improve quality of life [46], the pathways of recovery need further investigation. A prospective mixed-methods cohort study might reveal possible interventions to target for future studies.…”
Section: Plos Onementioning
confidence: 99%
“…As of 15 May 2020, 4 405 680 coronavirus 2019 (COVID- 19) cases have been reported worldwide [1]. Although figures are increasing, it seems the virus aggression is lowering, significantly reducing the pressure on the intensive care unit (ICU) beds.…”
mentioning
confidence: 99%
“…Although PICS is a well-established finding in non-COVID-19 ARDS patients, its treatment is still under development [16,17]. Randomised controlled trials to date have not shown significant effects of post-ICU rehabilitation and exercise interventions [18][19][20]. Although patient's characteristics were considered to impact on the outcome of functional exercise performance in a secondary analysis of studies by DENEHY and co-workers [21,22], the programme content might be a more critical determinant of the lack of effectiveness.…”
mentioning
confidence: 99%
“…La réhabilitation respiratoire a montré des effets bénéfiques sur la capacité à l’exercice et la qualité de vie des patients après une infection à grippe H1N1 et elle est recommandée après une exacerbation de bronchopneumopathie chronique obstructive. L’efficacité de la réhabilitation respiratoire après un SDRA demeure cependant incertaine [36] , [37] , [38] , [39] .…”
Section: Rôle Du Mk En Phase De Contagiosité Post-aiguëunclassified